ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENJUALAN MOTOR YAMAHA PADA PT HASJRAT ABADI - Marwana W; Muh Sabir (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to find out what factors dominate Yamaha Motorcycle Sales at PT. Hasjrat Abadi. The research method used is a descriptive research method, which is a research method that describes systematically, factual and accurately about the facts and characteristics of a certain population or tries to describe the phenomenon in detail. In this study, the data collection techniques used are questionnaires, interviews, and documentation. The results of this study show that the determining factor of Yamaha Motorcycle Sales at PT. Hasjrat Abadi is a promotional factor, then a price factor, a product factor, a place factor, a factor. Thus, of these five factors.